Carbon/SnO2/carbon core/shell/shell hybrid nanofibers : tailored nanostructure for the anode of lithium ion batteries with high reversibility and rate capacity - Kong, Junhua (2013)
A carbon/SnO2/carbon core/shell/shell hybrid nanofibrous mat was successfully prepared via single-spinneret electrospinning followed by carbonization and hydrothermal treatment. The morphology and structure of carbon/SnO2/carbon hybrid nanofibers were characterized by field-emission scanning electron microscopy, transmission electron microscopy, thermogravimetric analysis, wide-angle X-ray diffraction and X-ray photoelectron spectroscopy, and their electrochemical properties were studied as an anode in lithium ion batteries (LIBs). It is shown that the designed hybrid nanofibrous mat exhibits excellent electrochemical properties, including high reversible capacity with high columbic efficiency and impressive rate capacity. The greatly enhanced electrochemical performance is mainly due to the morphological stability and reduced diffusion resistance, which are induced by both the carbon core and deposited carbon skin. Furthermore, the embedded and de-aggregated SnO2 nanoparticles in the carbon phase, which are less than 10 nm in size, provide large numbers of reaction sites for lithium ions and ensure complete alloying with them.